(untitled) (International Journal of Engineering and Computer Science, 2018)
Direct memory access is process, which allows certain peripheral devices to access system memory without intervention of CPU. When CPU is performing I/O operation, it will occupy the entire duration of IOR/IOW operations and hence it is unavailable to do other operations. The DMAC is mainly helps in efficient utilization of hardware resources.